2010
DOI: 10.3382/ps.2009-00553
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and adrenal responses to various stressors in mule ducks from different commercial genetic selection schemes and their respective parental genotypes

Abstract: The mule duck, a hybrid produced by crossing a Muscovy drake and a Pekin female, is reported to express inappropriate behavior such as collective avoidance of people, the resulting distress and physical consequences potentially compromising their welfare. The present study was carried out to characterize the responses of mule duck strains from different commercial selection schemes to various stressful conditions and to confirm previous data on the genetic cross effects observed in a specific genotype. Three i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Indeed, such selection might reduce the buffer capacity of the animal in its reaction to stress (Rauw, 2007 ). Mule ducks are known to have a high sensitivity to stress, high social motivation, and a high level of fear of humans (Arnaud et al., 2010 ; Guéméné et al., 2006 ; Marie-Etancelin et al., 2008 ). Our results indicate that selection for lower RFI increases vocal expression during novelty investigation and lowers vocal reactivity to a human.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such selection might reduce the buffer capacity of the animal in its reaction to stress (Rauw, 2007 ). Mule ducks are known to have a high sensitivity to stress, high social motivation, and a high level of fear of humans (Arnaud et al., 2010 ; Guéméné et al., 2006 ; Marie-Etancelin et al., 2008 ). Our results indicate that selection for lower RFI increases vocal expression during novelty investigation and lowers vocal reactivity to a human.…”
Section: Discussionmentioning
confidence: 99%
“…more fearful than the two parents for fear of man at 10 weeks of age) (Faure et al., 2003 ). Other studies suggested that Domestic ducks respond to fear and stress with a general increase in behavioural activity and physiological responses, while Muscovy ducks showed increased avoidance behaviour (Arnaud et al., 2008 , 2010 ).…”
Section: Assessmentmentioning
confidence: 99%